Inverkan av urbana grönområden på människors hälsa - Sjetne, Caroline (2015)
Both mental and physical ill health, population and urbanization is increasing both in the world and in Sweden. These are challenges that politicians and city planners in today's society should take into account when it is expected to cause problems in the future regarding the economy and human health. To highlight efforts to improve public health, the main objectives of this study is to examine the evidence regarding the relationship between the available green space in urban environments and people's physical and mental health. The method is a systematic literature review based on 19 scientific articles. The result shows four main areas: Physical activity linked to green areas accessibility, physical activity in green areas linked to mental health, mental health linked to green spaces and restorative effects. The result shows that the availability of green areas is important for the frequency of visits. The studies found that mental health improvements were made both in natural habitats and in green areas in urban environments and also that rehabilitation through stay in nature can reduce depression and concentration difficulties, and promote prevention. The study concludes that there are clear links and impacts between natural / green areas, physical activity and mental health. By planning and making natural and green spaces available to people, it can provide and increasing the chances to use and thereby increase people's quality of life and reduce stress-related illness and sick leave. The results also suggest that external factors are necessary to take account of existing green areas. It requires more comprehensive and clinical research in the field. These findings could generate more reliable and concrete evidence regarding green spaces in urban environment's health benefits in the planning of cities.